(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Tatyana S. Borisova (Heraklion, Greece) The present paper deals with the book by Dimitry Tuptalo, Metropolitan of Rostov, titled “Runo Orošennoe” compared with the earlier work of the same author “Chuda Presviatij i Preblagoslovennoj Devy Marii” (The Miracles of the Holiest an the Most Blessed Virgin Mary”) as well as with the contemporary West European religious literature in the aspects of structure, language and symbolic and metaphoric images. The conscious orientation of Dimitry on the Byzantine and Church Slavonic canon as well as its creative interpretation based in the baroque framework are stressed. Key words: Baroque, Dimitry Tuptalo, Metropolitan of Rostov, “Runo Orošennoe”, symbols of the Holy Virgin, Church Slavonic language. DOI 10.23683/1995-0640-2019-1-58-66